Bcom ldan ʼdas Mi-ʼkhrugs-paʼi gzuṅs chog thar paʼi lcags kyu chog bsgrigs : a liturgical arrangement of Kun-mkhyen Padma-dkar-po's famed funeral practice of the Akṣobhyadhāraṇī - Bstan-ʼdzin-rnam-rgyal, Druṅ-yig (Kunjang Tobgeyl, 1979)
Ritual for the liturgical recitation of the formula (dharani) of the Tathagata Akshobhya; according to the Drukpa Kargyudpa tradition of Tibetan Buddhism.